Foresight and action learning supporting transition: An account of practice. Issue 2 (April 2021) - Beech, Nick; Gold, Jeff; Kershaw-Solomon, Hazel; Auty, Tricia; Down, Bruce; Goodchild, Joanne; Beech, Susan; Nisa, Shakiya
Integrating foresight into corporations has proved to be challenging. This account of practice reports on the introduction of futures and foresight (FF) teaching content into an executive Masters programme. The FF contentwas further linked to and provided a background for action learning sets. The purpose was to identify how introducing distant time horizons would help participants to adapt and change their perspectives in problem solving and professional development. The report describes how FF was incorporated across the programme and used to develop insightful conversations in the action learning sets. Citing two case examples, the authors reflect on how participants responded to these new elements and offer insights into the value of introducing FF as an interdisciplinary element in a programme.